2021
DOI: 10.1098/rsif.2020.0599
|View full text |Cite
|
Sign up to set email alerts
|

Spread of COVID-19 in urban neighbourhoods and slums of the developing world

Abstract: We study the spread of COVID-19 across neighbourhoods of cities in the developing world and find that small numbers of neighbourhoods account for a majority of cases ( k -index approx. 0.7). We also find that the countrywide distribution of cases across states/provinces in these nations also displays similar inequality, indicating self-similarity across scales. Neighbourhoods with slums are found to contain the highest density of cases across all cities under consideration, revealing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…It has been shown that the COVID-19 caseload, per million population and per km 2 , is systematically higher in high-density areas compared with lower-density areas. [21] A limitation of the present study is that we do not have any data from private laboratories, which serve a different, wealthier population.…”
Section: Researchmentioning
confidence: 98%
“…It has been shown that the COVID-19 caseload, per million population and per km 2 , is systematically higher in high-density areas compared with lower-density areas. [21] A limitation of the present study is that we do not have any data from private laboratories, which serve a different, wealthier population.…”
Section: Researchmentioning
confidence: 98%
“…It has been shown that COVID-19 caseload per million population and per square kilometre are systematically higher in high density areas compared to lower density areas. [21] . A limitation of this study is that we do not have any data from private laboratories which serve a different, wealthier population.…”
Section: Discussionmentioning
confidence: 99%
“…The negative relationship between economic stress and mental health is one of the "most consistently replicated ndings in the social sciences" [48]. Economic stress impacts mental health through multiple mechanisms-unemployment, nancial threat, indebtedness, economic hardship, volatility in income, deterioration in living standard and decreased levels of welfare support [49][50][51][52]. The psychological impact of economic stress increases under times of economic recession and macroeconomic shocks [49,52], manifesting itself in increased levels of depression, anxiety and depression [53].…”
Section: Discussionmentioning
confidence: 99%